Place Identity: How Far Have We Come in Exploring Its Meanings? - Peng, Jianchao; Strijker, Dirk; Wu, Qun (Frontiers in Psychology, 2020)
In order to synthesize the extensively studied place identities and their meanings, this paper reviews how researchers have conceived and deconstructed place identity. CiteSpace, a scientometric tool for visualizing and analyzing trends and patterns in scientific literature, is used to identify the active topics and new developments of publications in place identity. The dataset input into CiteSpace consists of 1,011 bibliographic records retrieved from the core database of Web of Science with a title search of the articles published between 1985 and July 2019. The scientometric review reveals the extensive applications of place identity in various topics. Studies in this field experienced an active exploration in plural disciplines after 2000, and the hot area gradually concentrated on the discipline of humanities and social sciences after 2010 and shifted towards place marketing until now. A network of co-cited references identified seven dominant research clusters, of which the research on the influence of place identity on social actors’ attitudes and behaviors is most prominent and the research on the effects of physical environment change on place identity captures the latest emerging area. Versatile meanings of place identity are witnessed in different clusters and articles of a cluster. These meanings are intertwined in shaping the knowledge base of thematic concentrations. To supplement the scientometric analysis, a deep survey on measuring methods and roles of place identity in contents of academic articles are made to trace knowledge connections between different empirical understandings of place identity. Finally, this paper summarizes the meanings of place identity in four dimensions and in turn offers some suggestions for further research directions.